Proposed Modifications to the Egyptian Concrete Code Based on a Comprehensive Sustainability Assessment of Portland Cement Alternatives for Climate Change Mitigation - ElHakim, Yasmin (AUC Knowledge Fountain, 2026)
Climate change is a major challenge facing planet earth today. This phenomenon is foreseen to continue to represent a major concern for decades to come. The construction industry is one of the most polluting sectors worldwide and is considered one of the top greenhouse gas emitters. Egypt, in particular, is one of the most vulnerable countries to the adverse effects of climate change. The construction sector plays a major role in Egypt’s economy, contributing significantly to the national GDP, yet it also represents one of the country’s largest greenhouse gas emitters. However, the Egyptian Concrete Code does not enforce the use of sustainable materials and does not recommend or mandate the application of green rating systems. Efforts to mitigate climate change within the construction industry are scattered, weakly coordinated, and insufficiently monitored. Moreover, most existing research focuses primarily on the environmental dimensions of different Portland cement alternatives, often limited to assessing carbon emissions, without evaluating a broader range of environmental impacts. Furthermore, governance factors and ways for the implementation of green practices are usually studied separately. Therefore, there is a research gap in assessing Portland cement alternatives within the frame of sustainability, considering the four sustainability pillars, which are environmental, economic, social, and institutional. Consequently, this work aims to conduct a comprehensive sustainable assessment, including the four sustainability pillars, namely, environmental, social, economic and institutional, for Portland cement, blended cement with ground granulated blast furnace slag, silica fume, and metakaolin. Based on the outcomes of this analysis, this study recommends an evidence-based framework to incorporate supplementary cementitious materials into codes and policies. After that, it recommends amendments to the Egyptian concrete code to incorporate supplementary cementitious materials and to include provisions for sustainable development as a a strategy for climate mitigation. The environmental analysis was performed using Life Cycle Assessment (LCA) through SimaPro software, applying the ReCiPe technique at both the midpoint and endpoint levels. The socio-economic analysis utilized environmental pricing data developed by CE Delft, adapted to Egyptian market conditions. The economic analysis considered market prices and hazard repair costs to reflect long-term financial implications. Based on the findings of these assessments, recommendations for the institutional pillar were formulated, particularly regarding amendments to the Egyptian Concrete Code. It was concluded that blended cement with 30% slag is the optimum sustainable material, and it is recommended to be mandated for use in the Egyptian concrete code. Blended cement with silica fume ranked second and is recommended for mandatory use in the Egyptian concrete code, especially under harsh conditions. Followed by metakaolin blended cement, which is recommended to be incentivized in the Egyptian concrete code. Overall, the results proved that the use of partial cement replacement with materials such as slag, silica fume, and metakaolin has promising effects on the environment, society, and the economy. Therefore, this work is pioneering in incorporating all four sustainability pillars in analyzing the potential use of supplementary cementitious materials while also proposing institutional mechanisms to support their implementation and enforcement.